A prospective study of clinical outcomes of HIV-associated and HIV-negative Kaposi sarcoma in Uganda. (1st January 2023) - Phipps, Warren; Adams, Scott V.; Mooka, Peter; Kafeero, James; Sekitene, Semei; Mubiru, Dennis; Nankoma, Janet; Namirembe, Constance; Okoche, Lazarus; Namubiru, Elizabeth B.; Kayemba, Shadiah; Baker, Kelsey K.; et al.
Abstract : Objective: Improved understanding of the effect of HIV infection on Kaposi sarcoma (KS) presentation and outcomes will guide development of more effective KS staging and therapeutic approaches. We enrolled a prospective cohort of epidemic (HIV-positive; HIV + KS) and endemic (HIV-negative; HIV − KS) KS patients in Uganda to identify factors associated with survival and response. Methods: Adults with newly diagnosed KS presenting for care at the Uganda Cancer Institute (UCI) in Kampala, Uganda, between October 2012 and December 2019 were evaluated. Participants received chemotherapy per standard guidelines and were followed over 1 year to assess overall survival (OS) and treatment response. Results: Two hundred participants were enrolled; 166 (83%) had HIV + KS, and 176 (88%) were poor-risk tumor (T1) stage. One-year OS was 64% (95% confidence interval [CI] 57–71%), with the hazard of death nearly threefold higher for HIV + KS (hazard ratio [HR] = 2.93; P  = 0.023). Among HIV + KS, abnormal chest X-ray (HR = 2.81; P  = 0.007), lower CD4 + T-cell count (HR = 0.68 per 100 cells/μl; P  = 0.027), higher HIV viral load (HR = 2.22 per log10  copies/ml; P  = 0.026), and higher plasma Kaposi sarcoma-associated herpesvirus (KSHV) copy number (HR = 1.79 per log10  copies/ml; P  = 0.028) were associated with increased mortality. Among HIV − KS, factors associated with mortality included Karnofsky score <70 (HR = 9.17; P  = 0.045), abnormal chest X-ray (HR = 8.41; P  = 0.025), and higher plasma KSHV copy number (HR = 6.21 per log10  copies/ml; P  < 0.001). Conclusions: Although survival rates were better for HIV − KS than HIV + KS, the high mortality rate seen in both groups underscores the urgent need to identify new staging and therapeutic approaches. Factors associated with mortality, including high plasma KSHV, may serve as important targets of therapy.